2020
DOI: 10.1088/1741-2552/ab933d
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and biological characterization of thin-film platinum-iridium alloy electrode coatings: a chronic in vivo study

Abstract: Objective. To evaluate the electrochemical properties, biological response, and surface characterization of an electrodeposited Platinum-Iridium (Pt-Ir) electrode coating on cochlear implants subjected to chronic stimulation in vivo. Approach. Electrochemical impedance spectroscopy (EIS), charge storage capacity (CSC), charge injection limit (CIL), and voltage transient (VT) impedance were measured bench-top before and after implant and in vivo. Coated Pt-Ir and uncoated Pt electrode arrays were implanted into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 61 publications
3
14
0
Order By: Relevance
“…That is why, for this group of samples, the growth of FC should be expected with longer implantation. The observed results correlated with recent work of Dalrymple et al [ 61 ], which showed that Pt–Ir-coated steel electrodes became fibrotic during cochlear implantation and the capsule thickness slightly increased after 5 weeks of implantation. This was detected by an increase in the impedance, while no histological data were obtained.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…That is why, for this group of samples, the growth of FC should be expected with longer implantation. The observed results correlated with recent work of Dalrymple et al [ 61 ], which showed that Pt–Ir-coated steel electrodes became fibrotic during cochlear implantation and the capsule thickness slightly increased after 5 weeks of implantation. This was detected by an increase in the impedance, while no histological data were obtained.…”
Section: Resultssupporting
confidence: 91%
“…The maturation of FC by 3 months due to the thickening and compaction of connective tissue fibers synthesized by fibroblasts led to a decrease in their average thickness. Our results show that implants with noble metal coatings caused the formation of a dense fibrous capsule with a minimal level of immune response from the very beginning, which was consistent with the abovementioned data obtained for PtIr electrodes [61]. In this case, the increase in FC over time observed for samples with PtIr coating may have been due to the nonspecific toxic effect of Pt ions leaching from their surface, when the death of fibroblasts inside the capsule led to the start of the repair mechanism and the formation of a new layer of the fibrous capsule.…”
Section: Average Thickness Of the Fibrous Capsulesupporting
confidence: 92%
“…Pt electrodes, which are more clinically-relevant, also exhibit more capacitive behaviour at low frequencies, indicated by a phase closer to -90°. This behaviour has been reported in several in vivo studies using Pt electrodes, in which the low frequency (1 Hz) impedance phase was approximately -66° (Shepherd et al, 2021) and the 100 Hz impedance phase ranged from -56° to -72° (Dalrymple et al, 2020a(Dalrymple et al, , 2020bShepherd et al, 2021). This is similar to how the stainless steel electrode behaved here, suggesting that the Injectrode may also accumulate less charge than a Pt electrode.…”
Section: The Injectrode ® For Drg Stimulationsupporting
confidence: 87%
“…Gold or platinum are more appropriate than silver for chronic implants because they are biocompatible and are less likely to elicit a strong tissue response (Wellman et al, 2018). A strong tissue response would increase the impedance at the electrode-tissue interface, thereby requiring more charge injection to effectively stimulate the neural target (Cogan, 2008;Dalrymple, 2021;Dalrymple et al, 2020a). The Injectrode design is promising for chronic use as it conforms to the tissue around it, limiting the potential for compression of nearby structures, like the DRG, as compared to stiffer electrode leads currently used for DRG stimulation.…”
Section: Limitations Relevance and Translation To Humansmentioning
confidence: 99%
“…43 Moreover, unlike metal electrodes, conductive polymers are also capable of preventing skin injuries. 34 CPs are being extensively studied as a method to mitigate limitations aforementioned in miniaturization due to their beneficial characteristics such as biocompatibility, environmental 17 Cassar et al, 18 Dalrymple et al 19 Aurum Biocompatibility, good conductivity Kim et al 20 Iridium oxide Good biostability, high charge storage capacity Hasenkamp et al 21…”
Section: Conductive Polymersmentioning
confidence: 99%